Technological frontiers and optimization in solar power towers: innovations in thermal energy storage, receivers, and heliostat systems - Zeshan Aslam; Syed Ihtsham Ul Haq Gilani; Taib Iskandar Mohamad; Masdi Muhammad; Kehinde Temitope Alao (Clean Technologies and Environmental Policy, 2025)

Adoption of prescriptive analytics for naval vessels risk-based maintenance:A conceptual framework - Mohd Adha Mat Esa; Masdi Muhammad (Ocean Engineering, 2023)

Feasibility Study of Harnessing Low Wind Speed Turbine as Hybrid Power Source for Offshore Platforms - Izleena Md Iqbar; Masdi Muhammad; Syed Ihtsham Ul-Haq Gilani; Frank Adam (Journal of Marine Science and Engineering, 2022)
In this study, the viability of harnessing wind energy for offshore oil and gas (O&G) platforms as a micro-grid solution in low wind speed regions to power O&G platforms is explored. However, wind, as a renewable energy, is known to be highly variable and is unable to provide standalone power reliably within a micro-grid solution due to the variation of the wind speed at hub height, which subsequently leads to a variation of the power outcome. Here, a hybrid power generation concept is developed in which one gas turbine generator (GTG) is replaced with a floating horizontal axis wind turbine (WT) system. By setting up this system, the reduction of the maintenance costs of the GTGs and the reduction of fuel gas consumption reduces carbon dioxide (CO2) emissions. In addition to this, the fuel gas savings in terms of the business side of such a solution provide a positive revenue impact. In this feasibility study, a technical framework is developed, followed by an economic framework. In the technical framework, wind assessments are performed to obtain the annual energy production for the selected field. Furthermore, an economic framework is established for both conventional and hybrid concepts in two scenarios: greenfield and brownfield, where the incremental net present value (NPV) and levelized cost of energy are calculated. The resultant difference in NPV for hybrid power generation compared to conventional power generation was found to be between 22% and 37%. The levelized cost of energy (LCOE) for WT is USD 165.52/MWh, which is 39% lower than for conventional, gas turbine-only operations. The LCOE for the hybrid approach is lower than for the conventional scenario by 22%. In conclusion, the hybrid micro-grid concept solution can harness wind energy from low wind regions with better economic benefits compared to conventional methods through the proper selection of the WT system, its floating substructure, and efficient micro-grid system for powering oil and gas platforms.